2010
DOI: 10.19173/irrodl.v11i1.769
|View full text |Cite
|
Sign up to set email alerts
|

Profiles in self-regulated learning in the online learning environment

Abstract: Individuals who are self-regulated in their learning appear to achieve more positive academic outcomes than individuals who do not exhibit self-regulated learning behaviors. We suggest that distinct profiles of self-regulated learning behaviors exist across learners. In turn, these profiles appear to be associated with significantly different academic outcomes. The purpose of the current study was to examine whether profiles for self-regulated learning skills and strategies exist among learners. To achieve thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
0
20

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(167 citation statements)
references
References 31 publications
9
138
0
20
Order By: Relevance
“…Therefore, we suggest that course developers would be well advised to ensure that first-year students are adequately trained, and directed towards the use of key learning resources as well as informed of the relationship between resource use and grades. Furthermore, as resource utilisation may be linked to students' proficiency to self-regulate their learning, as suggested by prior research (Azevedo, Cromley, and Seilbert 2004;Barnard-Brak, Lan, and Paton 2010;). Therefore, mechanisms for assisting students with their development of self-directed study skills should be included in learning environment design.…”
Section: Resultsmentioning
confidence: 80%
“…Therefore, we suggest that course developers would be well advised to ensure that first-year students are adequately trained, and directed towards the use of key learning resources as well as informed of the relationship between resource use and grades. Furthermore, as resource utilisation may be linked to students' proficiency to self-regulate their learning, as suggested by prior research (Azevedo, Cromley, and Seilbert 2004;Barnard-Brak, Lan, and Paton 2010;). Therefore, mechanisms for assisting students with their development of self-directed study skills should be included in learning environment design.…”
Section: Resultsmentioning
confidence: 80%
“…Motivation is an important part of the SRL. Specifically, intrinsic motivation is needed to perform learning tasks as part of the forethought, the strategic process that precedes performance in learning [8]. However, it is more feasible to understand the reasons that may lead a person to consider undertaking a MOOC.…”
Section: Methodology: Learners' Motivationmentioning
confidence: 99%
“…According to Barnard-Brak et al [4], self-regulated learning refers to volitional behaviours on individual learners part to succeed in their learning. Those behaviours include but not limited to the following: setting up study goals (goal setting), strategising effective way of solving the task given (task strategies), planning an effective managing study time (time management), deciding on location of study to acquire optimum benefit with low distractions (environment structuring), requesting for assistance from peers and tutors in providing help in area of concern (help seeking) and lastly self-reflection on personal studies to evaluate the goals achieved (selfevaluation).…”
Section: Background Of Self-regulated Learningmentioning
confidence: 99%
“…Research shows that one of the causes of the low completion rate in MOOC could be due to the lack of motivation and procrastination within the learners to self-regulate and engage consistently with the course [2]. It has been known that learners who exhibit the ability to self-regulate their learning perform better academically as compared to learners with non or minimal self-regulated learning skills [3,4]. This research described the self-regulated learning ability identified among different learners' modes of study.…”
Section: Introductionmentioning
confidence: 99%